GAME RPG “GARUDA QUEST” BERTEMAKAN MITOLOGI INDONESIA BERBASIS ANDROID - Dermawan, Ichwan; Ulya Anisatur Rosyidah; Habibatul Azizah Al Faruq (Computer Science and Information Technology, 2025)
With the high interest of generation Z in Indonesia in mobile games, this opportunity can be used to introduce various local mythological creatures. One way that can be done is by designing a role-playing game with the theme of Indonesian mythology, which can be played on the Android platform with the game name 'Garuda Quest'. This game was developed using the MDLC (Multimedia Development Life Cycle) method, this method has 6 stages, namely concept, design, material collecting, assembly, testing and distribution. The test results using black box testing show that all the functionalities of the "Garuda Quest" game features run well. The trial on 50 respondents showed that the percentage of feature feasibility was 85.52% and the percentage of playing experience was 82.48%, which shows that the game "Garuda Quest" was well received.